2019
DOI: 10.1161/circresaha.118.314030
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging Visualizes Recruitment of Inflammatory Monocytes and Macrophages to the Injured Heart

Abstract: Rationale: Paradigm shifting studies have revealed that the heart contains functionally diverse populations of macrophages derived from distinct embryonic and adult hematopoietic progenitors. Under steady state conditions, the heart is largely populated by CCR2-macrophages of embryonic descent. Following tissue injury, a dramatic shift in macrophage composition occurs whereby CCR2+ monocytes are recruited to the heart and differentiate into inflammatory CCR2+ macrophages that contribute to heart failure progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 40 publications
5
79
0
Order By: Relevance
“…In addition, a recent study using scRNA-Seq demonstrated the existence of multiple populations of resident and recruited macrophages in mouse lung airspace under healthy and acute inflammatory conditions; these macrophage populations exhibited distinct transcriptional profiles relevant to the inflammatory process [33]. As in the cardiac study [32], these macrophage populations were identified using unsupervised clustering and analysis of classical inflammatory and reparative markers [33]. Similar studies in atherosclerosis in mice and steady-state human liver, among other tissues, have found similar results: macrophages have been grouped into multiple and distinct populations using unsupervised clustering based on gene expression profiles; based on known phenotypic marker genes coupled to experimental analysis relying on the reduction or exacerbation of disease phenotypes, such macrophage populations were grouped to reflect distinct presumed functions [28,29].…”
Section: Single-cell Transcriptomics Reveals Macrophage Subpopulationmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, a recent study using scRNA-Seq demonstrated the existence of multiple populations of resident and recruited macrophages in mouse lung airspace under healthy and acute inflammatory conditions; these macrophage populations exhibited distinct transcriptional profiles relevant to the inflammatory process [33]. As in the cardiac study [32], these macrophage populations were identified using unsupervised clustering and analysis of classical inflammatory and reparative markers [33]. Similar studies in atherosclerosis in mice and steady-state human liver, among other tissues, have found similar results: macrophages have been grouped into multiple and distinct populations using unsupervised clustering based on gene expression profiles; based on known phenotypic marker genes coupled to experimental analysis relying on the reduction or exacerbation of disease phenotypes, such macrophage populations were grouped to reflect distinct presumed functions [28,29].…”
Section: Single-cell Transcriptomics Reveals Macrophage Subpopulationmentioning
confidence: 81%
“…Specifically, although a small population of resident CCR2 + macrophages could be identified even in uninjured hearts, the increase in visualized CCR2 signal after MI in mice was dramatic and could be easily distinguished from baseline. In addition, this probe was capable of detecting CCR2 + monocytes and macrophages in humans post-MI and in chronic ischemic cardiomyopathy, thus providing proof of concept for the development of putative biomarkers and targeted treatments based on CCR2 [32].…”
Section: Single-cell Transcriptomics Reveals Macrophage Subpopulationmentioning
confidence: 98%
“…Previously, we reported the capacity of a targeted PET tracer to quantify the CCR2-specific inflammation burden in multiple animal models using ECL1i peptide through 64 Cu or 68 Ga radiolabel (7)(8)(9). The PET signal intensity in inflammatory tissues was corroborated by molecular characterization of CCR2 expression and correlated with disease progression and regression.…”
Section: Introductionmentioning
confidence: 85%
“…The TIMD4 + and TIMD4 - subgroups were reduced in the early phase post MI but gradually increased via self-renewal 71 . 68 Ga-DOTA-ECL1i, a PET radiotracer, could specifically bind to CCR2 + monocytes/macrophages, and the signal was correlated with CCR2 + abundance, which provided an effective molecular imaging method to noninvasively visualize the recruitment of monocytes and macrophages to the infarct heart 72 .…”
Section: Immune Cellsmentioning
confidence: 99%